Experience of tricuspid valve replacement: immediate and long-term results - G.I. Darwish; M.F. Rotari; N.S. Gnoianko (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the efficiency and safety of tricuspid valve replacement (TVR) either as an isolated procedure or in combination with other procedures. Materials and methods. This study focused exclusively on patients who had TVR as an isolated procedure or in combination with other cardiac surgery interventions. The data of 33 patients were analyzed (period from May 2010 to August 2019). Bioprosthetic replacement of the tricuspid valve was performed in all cases.